2009
DOI: 10.2298/tsci0904213a
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection heat transfer in a partially divided trapezoidal enclosure

Abstract: Natural convection heat transfer in a partially divided trapezoidal enclosure is studied numerically using the control volume method. Summer and winter conditions are separately examined by imposing regarding thermal boundary conditions. A horizontal divider included and its two different placements are considered. It is shown that heat transfer results are not significantly altered by the presence of the divider for summer condition. For winter condition, on the other hand, decrement in heat loss and effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Furthermore, there are wide disagreements among correlations and lack of information even for simpler configurations of horizontal or vertical layers, as will be shown later. Relevant and practical studies can be found in literature [13][14][15][16]. Figure 1 shows the geometry of the present numerical study.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are wide disagreements among correlations and lack of information even for simpler configurations of horizontal or vertical layers, as will be shown later. Relevant and practical studies can be found in literature [13][14][15][16]. Figure 1 shows the geometry of the present numerical study.…”
Section: Introductionmentioning
confidence: 99%
“…Lam et al [1], presented experimental and numerical studies of free convection in trapezoidal enclosures constructed of two vertical isolated side walls, a horizontal hot bottom wall and an inclined cold top wall. Arici and Sahin [2] numerically investigated the natural convection in a partially divided trapezoidal enclosure by using the control volume method. The investigation is done for two different placements of a divider to gether with a non-divider enclosure.…”
Section: Introductionmentioning
confidence: 99%